О “возвратных” существительных в старобелорусском языке - Закарьян, М. (Kalbotyra, 1976)
In Old Byelorussian written monuments there occur verbal nouns in -нье/-енье (-nje/-enje) with the reflexive formant -ся (-s’a). They are built exclusively from reflexive verbs, and they have a purely processive meaning. These nouns show up in the writings from the beginning of the sixteenth century, proliferating in the language of the religious and polemic writings from the late sixteenth - mid-seventeenth centuries.